2010
DOI: 10.1111/j.1745-4530.2009.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High‐pressure Homogenization on the Functional Property of Peanut Protein

Abstract: The effect of high‐pressure homogenization (HPH) at 0.1 (control), 40 or 80 MPa on the denatured peanut protein were investigated. Solubility, emulsifying property, foaming property, differential scanning calorimetry (DSC) characteristic, water‐holding capacity (WHC) and scanning electron microscope (SEM) analysis of the peanut protein isolates (PPIs) from the peanut flour after various HPH treatments were analyzed. Increased solubility of the denatured peanut protein by HPH treatment depended on the pH value.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 36 publications
6
22
0
Order By: Relevance
“…HPH is widely applied in food industry. Characteristics of food materials were modified by (ultra) HPH technique, such as ice cream mixes (Innocente et al, 2009), tomato juices (Bot et al, 2017), soy milk (Cruz et al, 2007), milk (Zamora et al, 2007), soybean protein (Song et al, 2013;Liu & Kuo, 2016), myofibrillar protein (Chen et al, 2017) and peanut protein (Dong et al, 2011). When the processed fluid is forced through the very narrow high-pressure valve gap, particles can be ruptured by the mechanical associated forces inducing a significant reduction in size down to the micron/submicron range (Paquin, 1999;Floury et al, 2003Floury et al, , 2004Thiebaud et al, 2003;Cort es-Muñoz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPH is widely applied in food industry. Characteristics of food materials were modified by (ultra) HPH technique, such as ice cream mixes (Innocente et al, 2009), tomato juices (Bot et al, 2017), soy milk (Cruz et al, 2007), milk (Zamora et al, 2007), soybean protein (Song et al, 2013;Liu & Kuo, 2016), myofibrillar protein (Chen et al, 2017) and peanut protein (Dong et al, 2011). When the processed fluid is forced through the very narrow high-pressure valve gap, particles can be ruptured by the mechanical associated forces inducing a significant reduction in size down to the micron/submicron range (Paquin, 1999;Floury et al, 2003Floury et al, , 2004Thiebaud et al, 2003;Cort es-Muñoz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, food functional improvements induced by (ultra) HPH have attracted great interest. Characteristics of food materials were modified by (ultra) HPH technique, such as ice cream mixes (Innocente et al, 2009), tomato juices (Bot et al, 2017), soy milk (Cruz et al, 2007), milk (Zamora et al, 2007), soybean protein (Song et al, 2013;Liu & Kuo, 2016), myofibrillar protein (Chen et al, 2017) and peanut protein (Dong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In general, using high pressure and temperature during homogenization was led to decrease protein solubility due to conformal changes of proteins resulted in protein aggregation and/or precipitation during homogenization process (Dhakal et al, 2014). However, Dong et al (2011) and Dhakal et al (2014) stated that there was a slight increase in protein solubility in peanut proteins up to 750 bar and in almond milk up to 1,500 bar, respectively. Lakshmanan, de Lamballerie, and Jung (2006) and Dhakal et al (2014) reported that the solubility of protein in soymilk and almond milk was decreased after heating treatments at 95 and 85 8C, respectively.…”
Section: Protein Solubilitymentioning
confidence: 99%
“…Cavitation, shear, turbulence, and temperature rise affect protein conformational structure, thereby modifying the functionalities (Dumay et al, ; Ye & Harte, ). It has been reported that HPH was performed to modify structural and functionalities of various proteins including dairy proteins (Ali et al, ; Iordache & Jelen, ; Lee, Lefèvre, Subirade, & Paquin, ; Ye & Harte, ), plant proteins (Dong et al, ; Liu & Kuo, ; Song, Zhou, Fu, Chen, & Wu, ; Sun, Dai, Liu, & Gao, ; Yang, Liu, Zeng, & Chen, ), meat proteins (Saricaoglu, Gul, Tural, & Turhan, ) and our previous findings in shellfish proteins (Yu, Cha et al, ; Yu, Wu, Cha, Qin, & Du, ; Yu, Wu, Cha, Zou et al, ). It has also been reported that HPH treatment has potential application for improving the functionality of muscle proteins in water to develop new meat‐based products in food industry (Chen, Xu, & Zhou, ; Chen, Zhou, Xu, Zhou, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%